Becoming African Americans : Black public life in Harlem, 1919-1939 - Corbould, Clare (Harvard University Press, 2009)
Africa has always played a role in black identity, but it was in the tumultuous period between the two world wars that black Americans first began to embrace a modern African American identity. Throwing off the legacy of slavery and segregation, black intellectuals, activists, and organizations sought a prouder past in ancient Egypt and forged links to contemporary Africa. Their consciousness of a dual identity anticipated the hyphenated identities of new immigrants in the years after World War II, and an emerging sense of what it means to be a modern American.